Associations of father and adult male presence with first pregnancy and HIV infection: Longitudinal evidence from adolescent girls and young women in rural South Africa (HPTN 068) - Albert, Lisa M; Edwards, Jess; Pence, Brian; Hills, Susan; Kahn, Kathleen; Gómez‑Olivé, F. Xavier; Wagner, Ryan G; Twine, Rhian; Pettifor, Audrey (Springer, 2021)
This study, a secondary analysis of the HPTN 068 randomized control trial, aimed to quantify the association of father and male presence with HIV incidence and first pregnancy among 2533 school-going adolescent girls and young women (AGYW) in rural South Africa participating in the trial between March 2011 and April 2017. Participants’ ages ranged from 13–20 years at study enrollment and 17–25 at the post-intervention visit. HIV and pregnancy incidence rates were calculated for each level of the exposure variables using Poisson regression, adjusted for age using restricted quadratic spline variables, and, in the case of pregnancy, also adjusted for whether the household received a social grant. Our study found that AGYW whose fathers were deceased and adult males were absent from the household were most at risk for incidence of first pregnancy and HIV (pregnancy: aIRR = 1.30, Wald 95% CI 1.05, 1.61, Wald chi-square p = 0.016; HIV: aIRR = 1.27, Wald 95% CI 0.84, 1.91, Wald chi-square p = 0.263) as compared to AGYW whose biological fathers resided with them. For AGYW whose fathers were deceased, having other adult males present as household members seemed to attenuate the incidence (pregnancy: aIRR = 0.92, Wald 95% CI 0.74, 1.15, Wald chi-square p = 0.462; HIV: aIRR = 0.90, Wald 95% CI 0.58, 1.39, Wald chi-square p = 0.623) such that it was similar, and therefore not statistically significantly different, to AGYW whose fathers were present in the household.
Keywords: Pregnancy; HIV; Adolescent girls and young women